Amelioration of neuropilin-1 and RAGE/matrix metalloproteinase-2 pathway-induced renal injury in diabetic rats by rosuvastatin - Nabi, Rabia; Alvi, Sahir Sultan; Alouffi, Sultan; Khan, Saif; Ahmad, Adnan; Khan, Mahvish; Ahmad, Saheem; Khan, M. Salman (Archives of Biological Sciences, 2021)
Paper description: Alleviation of renal injury by rosuvastatin in streptozotocin-induced diabetes in rats was examined. Rosuvastatin administration ameliorated plasma carboxymethyl-lysine (CML) and the renal fluorescent-advanced glycation end-product (AGE) Transcription of RAGE, NFκB-2, TGF-β1 and MMP-2 was suppressed; the circulatory carbonyl content and paraoxonase-1 activity was ameliorated; renal histopathological features were attenuated, evidenced by improved glomerular appearance, Bowman’s space and abundant podocytes. The presented mechanistic insight into the role of rosuvastatin in attenuating diabetes-mediated renal dysfunction shows that rosuvastatin prevented AGE-induced renal injury via stimulation of neuropilin-1 expression and AGE-receptor (RAGE)/matrix metalloproteinase-2 signaling. Abstract: Advanced glycation end-products (AGEs) induce the production of reactive oxygen species (ROS) and extra cellular matrix (ECM) degradation via suppression of neuropilin-1 (NRP-1) and interaction with AGE-receptors (RAGE). This study aimed to reveal whether modulation of NRP-1 by rosuvastatin (RT) prevents AGE-induced renal injury via targeting RAGE/matrix metalloproteinase-2 (MMP-2) signaling in diabetic rats. Treatment with RT ameliorated the altered level of markers of glycemic control, renal injury, cholesterol, triglyceride (TG) and hepatic HMG-CoA reductase activity; the level of circulatory carboxymethyl-lysine (CML) and the accumulation of fluorogenic-AGEs in renal tissue was reduced; the expression of renal NRP-1, a checkpoint target, was stimulated; the transcription of RAGE, NFκB-2, TGF-β1 and MMP-2 was suppressed; the circulatory carbonyl content (CC) and paraoxonase-1 (PON-1) activity was ameliorated, and renal histopathological features were attenuated as evidenced by improved glomerular appearance, Bowman’s space and abundant podocytes in kidneys. In conclusion, RT exhibited the potential to counteract diabetes and AGE-induced renal pathologies via stimulation of NRP-1, suppression of RAGE, and of genes responsible for ECM disintegration (MMP-2) and the inflammatory response (NFκB-2).